HEALTH STATUS OF CLIMACTERIC WOMEN IN THE PRISON SYSTEM - Rita de Cássia Ferreira dos Santos; Audrey Vidal Pereira; Valdecyr Herdy Alves; Márcia Vieira dos Santos; Diego Pereira Rodrigues; Giovanna Rosário Soanno Marchiori (Cogitare Enfermagem, 2017)
The present study aimed to identify, based on reports, signs, symptoms and problems that affect the health of women in the climacteric period who are serving time in prison. Exploratory and descriptive study with a qualitative approach. Seven climacteric women incarcerated in a female prison in the State of Rio de Janeiro, Brazil, were interviewed from October 2014 to January 2015. After thematic analysis, two categories were identified: Symptoms related to the climacteric period and Problems that affect the health of women deprived of their liberty. Most interviewees reported feeling uncomfortable in the climacteric period, and having health problems in prison. Thus, climacteric, especially in situations of deprivation of liberty, should deserve greater attention of public health policies, to contribute to the improvement of the living conditions of this specific group